Relationship Between Nutritional Status And Incidence Of Anemia In Pregnant Women At The Bara-Baraya Health Center Makassar - Dwi Puspita, Winda; Khairat, Nur Ummul; Irwan, Hadriani; Aspar, Hukmiyah (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan Pelamonia, 2024)
Background: Nutritional status is influenced by the nutrients consumed so that it can show a person's nutritional status. Pregnant women are one of the groups that are vulnerable to nutritional problems so that the use of nutrients such as the essential microelement of iron that is not optimal during pregnancy can lead to anemia. The purpose of the study: this study was conducted to determine the relationship between nutritional status and the incidence of anemia in pregnant women at the Bara-Baraya Health Center Makassar. Type of research: This study uses an analytical method with a Cross Sectional Study to determine the relationship between nutritional status and the incidence of anemia in pregnant women at the Bara-Baraya Health Center Makassar with a population of 50 people and a total sample of 50 people using the Total Sampling technique. The results: Based on the results of the Chi-Square statistical test, the value of p = 0.02 < value of = 0.05 means that there is a relationship between nutritional status and the incidence of anemia in pregnant women at the Bara-Baraya Health Center Makassar. Conclusion: from these variables there is a relationship between the nutritional status variables and the incidence of anemia in pregnant women at the Bara-Baraya Health Center Makassar.